Studies on compatibility of white muscardine fungus Beauveria bassiana with some neem products - and S.N. SHARMA, PRAMILA GUPTA, M.S. PAUL (Indian Phytopathology, 2002)
The effect of seven commercial neem products (Margocide - 0.15% azadirachtin, Neem Gold - 0.15% azadirachtin, Neemark - 0.03% azadirachtin, Achook - 0.03% azadiradione, nimbocinol and epinimbocinol, Nimbicidine - 0.03% azadirachtin, Neemta 2100-0.15% azadirachtin and Field Marshal - 0.3% azadirachtin) at 10thin000, 1000 and 100 ppm with water or alcohol extracts of neem bark, neem leaves (dried) or neem cake (4 and 2%) was studied on the growth of Beauveria bassiana. Commercial formulations exhibited varying effects on the growth of B. bassiana ranging from inhibitory or neutral to stimulatory. It was concluded that Achook, Field Marshal, Margocide, Nimbicidine, neem cake and alcohol or water extracts of neem leaves can be used in combination withB. bassiana as part of an IPM strategy against selected pest species.